SISTEM INFORMASI KOPERASI BAGI KARYAWAN (KOPKAR) DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Widiarti, Dian; Subaida, Ida; Wahyuni, Ika (Growth, 2025)
Cooperatives for employees within an organization play a role in helping to improve welfare through various financial services. The aspect of management that is still conventional becomes one of the obstacles in the current digital era, where transparency and accountability are not maximally achieved. This research aims to design and develop a service application for employees of Universitas Abdurachman Saleh Situbondo named kopkar.id with the hope of becoming a solution in providing convenience for all cooperative members in monitoring and controlling savings and loan activities independently. Every step of the waterfall technique is fairly simple to follow, and the system is thoroughly documented once the stages are in place. Management of savings data, loans, transaction reports, and automatic notifications for participants are some of the most important functions of this application. After conducting research on this application, we concluded that this application improves operational efficiency and makes it easier for employees to obtain financial information in real-time. In addition, this application has a positive impact on transparency, accountability, and the trust of operational participants regarding operational failures. Therefore, the use of digital operational applications is effective in modernizing workplace operational systems.